(1/a-1/b)*((a+b)^2-a^2-b^2)/(a-b)^2)=
(1/a-1/b)*((a^2+2ab+b^2-a^2-b^2)/(a-b)^2)=
((1/a-1/b)*(2ab/(a-b)^2)=
((b-a)/ab)*(2ab/(a-b)^2)=
(-(a-b)/ab) *(2ab/(a-b)^2)=
-2/(а-b) =
2/(b-a)
ответ: 2/(b-a)
3) (a+b/a^2-ab-1/a):b/b-a
a(b/a-b-1):b/b-a (a-сокращаем)
(b/a-b-1):b/b
1) b-ab-a=b-ab
a
2) b-ab:b/b=ab(умноженная) b
3)0.5(умножен)7-2(умножен)7-2= -12,5
ответ: -12,5
+ b
)2 = a
2 + 2ab
+ b
2– квадрат суммы (a
– b
)2 = a
2 – 2ab
+ b
2– квадрат разностиa
2 – b
2 = (a
– b
)(a
+ b
)– разность квадратов (a
+ b
+ c
)2 = a
2 + b
2 + c
2 + 2ab
+ 2ac
+ 2bc
Формулы для кубов (a
+ b
)3 = a
3 + 3a
2b
+ 3a
b
2 + b
3– куб суммы (a
– b
)3 = a
3 – 3a
2b
+ 3a
b
2 – b
3– куб разностиa
3 + b
3 = (a
+ b
)(a
2 – ab
+ b
2)– сумма кубовa
3 – b
3 = (a
– b
)(a
2 + ab
+ b
2)– разность кубов
Формулы для четвёртой степени (a
+ b
)4 = a
4 + 4a
3b
+ 6a
2b
2 + 4a
b
3 + b
4(a
– b
)4 = a
4 – 4a
3b
+ 6a
2b
2 – 4a
b
3 + b
4a
4 – b
4 = (a
– b
)(a
+ b
)(a
2 + b
2)
Формулы для n
-той степени (a
+ b
)n
= an
+ na
n
– 1b
+ n
(n
– 1)a
n
– 2b
2 + ..+ n
!an – kbk
+ ..+ bn
2k
!(n – k
)!(a
– b
)n
= an
– na
n
– 1b
+ n
(n
– 1)a
n
– 2b
2 + ..+ (-1)k
n
!an – kbk
+ ..+ (-1)nbn
2k
!(n – k
)!